The effects of managerial entrenchments on the relationship between cash holdings and corporate financial objectives in GCC countries - Omar Ikbal Tawfik; Abdul Rahaman Abdul Rashid; Mohamed Maher Elbaz; Araby Madbouly (Cogent Business & Management)
Firms in the Gulf region are predominantly governed by the entrepreneurial model where royal ownerships/management dominants. Using a Panel Regression Model in a sample of 202 firms across six countries in the Gulf Cooperating Council (GCC), this paper assesses the direct effect of corporate cash holdings on firms’ financial objectives or performance, and also how managerial entrenchments directly affect corporate cash holdings in GCC. It further tests the moderation and interaction effects of managerial entrenchments on the relationship between cash-holdings and firms’ financial performance. The research concludes that the effect of corporate cash holdings on firms’ performance is negative, especially for absolute and relatively liquidity firms. This proofs the U-shape hypothesis of cash holdings. Also, the results show that different managerial entrenchment variables have different effects on corporate financial performance or objectives. Furthermore, the moderation and interaction effects of managerial entrenchment on the relationship between cash holding and firms’ financial performance (i.e. ROA and ROE) are inconsistent. These findings show randomness in how managerial entrenchment affects firms’ performance in the GCC region. However, the interaction between cash and leverage is consistently positive on shareholders wealth (i.e. ROE) for all liquidity thresholds. This highlights the benefits of debts in corporate financing.